Planck early results: VIII. The all-sky early Sunyaev-Zeldovich cluster sample - Ade, Peter A.; Bartelmann, Matthias; Schäfer, Björn Malte (Arxiv, 2011)
We present the first all-sky sample of galaxy clusters detected blindly by the Planck satellite through the Sunyaev-Zeldovich (SZ) effect from its six highest frequencies. This early SZ (ESZ) sample is comprised of 189 candidates, which have a high signal-to-noise ratio ranging from 6 to 29. Its high reliability (purity above 95%) is further ensured by an extensive validation process based on Planck internal quality assessments and by external cross-identification and follow-up observations. Planck provides the first measured SZ signal for about 80% of the 169 previously-known ESZ clusters. Planck furthermore releases 30 new cluster candidates, amongst which 20 meet the ESZ signal-to-noise selection criterion. At the submission date, twelve of the 20 ESZ candidates were confirmed as new clusters, with eleven confirmed using XMM-Newton snapshot observations, most of them with disturbed morphologies and low luminosities. The ESZ clusters are mostly at moderate redshifts (86% with z below 0.3) and span more than a decade in mass, up to the rarest and most massive clusters with masses above 10^15 Msol.
Gesehen am 22.09.2017